SMEs entrepreneurial finance-based digital transformation: towards innovative entrepreneurial finance and entrepreneurial performance - Yogesh Dwivedi (Venture Capital, 2024)
The antecedents and determinants of entrepreneurial capabilities and competencies remain one of the incontestable questions that drive the exploitation and discovery of effective financial and digital opportunities. In the present paper, we propose a conceptual model based on Kirzner’s alertness theory [entrepreneurial alertness] and rely on two factors [entrepreneurial orientation and marketing orientation] as key accelerators of entrepreneurial financial alertness. We assume that entrepreneurial financial alertness (EFA) might have a direct impact on entrepreneurial finance-based digital transformation (EFDT), which in turn, is expected to predict both innovation entrepreneurial finance (IEF) and SMEs’ entrepreneurial performance (SMEEP). Structural equation modeling (SEM) was employed using data collected from a purposive sample size of 214 Jordanian entrepreneurs. Our findings largely support the impact of EFA on EFDT. EFDT was also supported having a significant impact on both IEF and SMEEP. Our study has many implications for both researchers and practitioners in the area of entrepreneurial finance-based digital transformation. The study has great added-value by proposing and examining a solid theoretical foundation covering the most influential factors that drive digital entrepreneurial transformation as such transformation stands as an emerging and pressing issue, not fully tackled by prior studies.